The Global Natural Gas Market. Will transport cost reductions lead to lower prices? - Knut Einar Rosendahl; Eirik Lund Sagen (Statistics Norway, Research Department, 2007)
Reduced transportation costs are usually associated with lower import prices, increased trade and price convergence. In this paper we show that the lower costs can actually lead to higher import prices in some regions, and price divergence between import regions. Using both a general theoretical approach and a numerical model of the global natural gas market, we demonstrate that the price effect from transport cost reductions depend on the relative distances between regional markets, the choice of transport technology, and supply and demand responsiveness in the different markets. Our numerical results suggest that European consumers would generally be better off if pipeline costs are reduced, while North American consumers would be better off if LNG costs are reduced.
Keywords: C61; F17; L95; Q31; R40; 330; Natural gas; trade; transport costs; price convergence; numerical model